E-Schools Development In Filial Schools As A Solution To Improve Teaching And Learning Activities And The Effectiveness Of School Administration - Febrianty, Febrianty; Hadiwijaya, Hendra; Octafian, D. Tri (JPI (Jurnal Pendidikan Indonesia), 2020)
Lembaga Pembinaan Khusus Anak (LPKA) Class I Palembang is a pilot LPKA throughout Indonesia that has successfully implemented distance learning / filial schools with the same standards as the main schools (technical learning management schools) in collaboration with the Palembang City Education Office, Palembang City Government and Provincial Government of South Sumatra. LPKA Class I Palembang organizes formal education (filial schools) starting from elementary, middle, and high school levels. The purpose of this study is to build an e-school system as an alternative in overcoming problems in the teaching and learning process and academic administration of schools. The system development method used in this study is the Rapid Application Development (RAD) method, with the following stages: Requirements Planning, RAD Workshop Design, and Implementation. The results of this study are children's e-school systems so that it becomes a solution for LPKA Class I Palembang in implementing learning and improving the quality of children's learning.